2018
DOI: 10.1159/000489947
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Study of Percutaneous Trigeminal Compressive Balloon Positioning on Merged 3-D Rotational X-Ray and Preprocedural Magnetic Resonance Imaging

Abstract: Background: Percutaneous trigeminal rhizotomy or balloon compression for trigeminal neuralgia carries a potential risk for the brainstem, the carotid artery, and the basilar artery. Objective: To detail the relation of critical neural and vascular structures to expanded balloons used for percutaneous compression of the trigeminal ganglion. Method: A retrospective analysis of preprocedural magnetic resonance imaging (MRI) and procedural X-ray-based imaging for 9 patients detailed balloon proximity to the brains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…9 Long-term clinical practice has shown that if the quality of PBC surgery and effective "pear formation" is ensured, then better pain relief rates and lower recurrence rates can be obtained. [10][11][12] Traditional PBC surgery is performed under the guidance of X-ray or CT, [13][14][15][16][17] although lateral X-ray alone can only provide two-dimensional non-sectional images and cannot fully display the complex skull base bony structure and foramen ovale. However, using various improved CT-guided techniques 18,19 or surgery under electromagnetic navigation 20,21 still relies on the operator's free-hand operation and lacks the constraints of a fixed frame.…”
Section: Discussionmentioning
confidence: 99%
“…9 Long-term clinical practice has shown that if the quality of PBC surgery and effective "pear formation" is ensured, then better pain relief rates and lower recurrence rates can be obtained. [10][11][12] Traditional PBC surgery is performed under the guidance of X-ray or CT, [13][14][15][16][17] although lateral X-ray alone can only provide two-dimensional non-sectional images and cannot fully display the complex skull base bony structure and foramen ovale. However, using various improved CT-guided techniques 18,19 or surgery under electromagnetic navigation 20,21 still relies on the operator's free-hand operation and lacks the constraints of a fixed frame.…”
Section: Discussionmentioning
confidence: 99%